2020
DOI: 10.1177/0300060520980598
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction as the first sign of infective endocarditis: a case report

Abstract: Infective endocarditis is a bacterial or fungal infection of the heart valves or endocardial surface, and it frequently forms vegetation and can lead to systemic embolism. Dislodged vegetation rarely results in coronary artery embolism (CAE) and subsequent acute myocardial infarction. A 43-year-old male patient was emergently brought to our hospital for suspected acute myocardial infarction. Coronary angiography was performed and it showed embolism in the left circumflex artery. Thrombus aspiration was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Endocarditis of the mitral valve, Staphylococcus aureus or fungal infection, and vegetation size > 10 mm are predictors of coronary embolism in patients with infective endocarditis. 63 Marantic endocarditis also has been reported as an uncommon etiology of direct coronary embolism. 64 Among myxomas, those with a villiform surface, as opposed to smooth-surface myxomas, are more likely to be associated with direct coronary embolism.…”
Section: Resultsmentioning
confidence: 99%
“…Endocarditis of the mitral valve, Staphylococcus aureus or fungal infection, and vegetation size > 10 mm are predictors of coronary embolism in patients with infective endocarditis. 63 Marantic endocarditis also has been reported as an uncommon etiology of direct coronary embolism. 64 Among myxomas, those with a villiform surface, as opposed to smooth-surface myxomas, are more likely to be associated with direct coronary embolism.…”
Section: Resultsmentioning
confidence: 99%
“…Another peculiar cause of MINOCA is coronary embolisation of an endocardial vegetation fragment. Despite its rarity—observational studies have shown that the incidence of coronary embolism during infective endocarditis approximates 0.5%—, it constitutes a potentially lethal complication ( 51 ). Oftentimes, a septic embolus is not visible on coronary angiography owing to its microvascular localisation, but should be suspected in this specific clinical setting, especially in case of multiple embolic events.…”
Section: Risk Factors and Comorbiditiesmentioning
confidence: 99%